Pre-enrichment activation process of gallium-containing coal gangue

Through the pre-enrichment and activation process of a specific additive system, the problem of difficulty in activation after gallium enrichment in coal gangue is solved, and efficient enrichment and separation of gallium is achieved, reducing process complexity and cost.

CN119710308APending Publication Date: 2025-03-28INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311269435.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

After enrichment, gallium in coal gangue needs to be activated before leaching or ignition smelting can be carried out. The existing technology process is complex and costly, making it difficult to apply to industrial production.

Method used

A specific additive system is used to mix the degranulated coal gangue material with sodium, boron, aluminum and IIA/IVB element materials and sinter it after it is sintered to obtain pre-enriched and activated gallium-containing coal gangue sintered materials, achieving the enrichment and activation of gallium elements.

Benefits of technology

Through this process, the enrichment and activation effects of gallium in coal gangue are significant, and gallium is easier to separate and extract, reducing process complexity and cost, and improving the efficient utilization of gallium.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004475115150000131
    Figure BDA0004475115150000131
  • Figure BDA0004475115150000141
    Figure BDA0004475115150000141
Patent Text Reader

Abstract

The invention relates to a pre-enrichment activation process for gallium-containing coal gangue, which comprises the following steps: mixing a de-graded coal gangue material, a first auxiliary agent and a second auxiliary agent, and sintering to obtain a pre-enrichment activated gallium-containing coal gangue sintered material; the first auxiliary agent comprises a sodium material and a boron material; and the second auxiliary agent comprises an aluminum material and a magnesium material. According to the pre-enrichment activation process provided by the invention, the gallium element in the coal gangue can be enriched into a specific phase by virtue of a specific auxiliary agent system and aiming at the coal gangue raw material without complicated enrichment means such as sorting and flotation, and activation is realized at the same time, so that subsequent separation and extraction are facilitated, and various useful components can be effectively utilized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of secondary utilization of solid waste, and in particular to a pre-enrichment and activation process of gallium-containing coal gangue. Background Art

[0002] At present, coal is the basic energy to ensure my country's energy supply. Gangue is a mineral associated with coal. It is selected during the mining and processing process. The piled gangue occupies land, releases toxic gases and has the risk of spontaneous combustion, which is a huge harm to the local environment. At present, the main ways to use gangue in my country are: mining and backfilling, using it as a building material, power generation, agricultural fertilizer, road construction material and valuable element extraction.

[0003] For example, CN116286127A discloses a method for treating coal gangue, which comprises the following steps: step S1, crushing the coal gangue and flotation to collect organic components and inorganic components respectively; step S2, first using an acidic solution to remove Fe2O3, CaO and MgO in the inorganic components, and then pyrolyzing the inorganic components at 500-600°C to obtain ash; step S3, using an alkaline solution to remove SiO2 in the ash to obtain silicon-containing compounds and / or aluminum-containing compounds. The mass concentration of the acidic compound in the acidic solution is 0.5-3wt%. After this treatment, the organic components and inorganic components in the coal gangue are effectively utilized, and the organic components can be mixed into coal for combustion and power generation; the inorganic components can be used as high-purity silicon-aluminum raw materials, which are high-quality silicon-aluminum mineral resources.

[0004] Among them, gallium is a kind of scattered element widely distributed in coal. It has scarce reserves worldwide and cannot be mineralized alone. It is often found in the form of associated minerals. At present, the mainstream raw material for extracting gallium from coal-based resources is fly ash, which is a secondary raw material that enriches gallium to a certain extent after a series of treatments such as combustion of raw coal. Fly ash contains a large number of valuable metals such as iron, aluminum, lithium, gallium, rare earths, etc., especially gallium can be enriched to a grade of more than 100ppm after combustion of raw coal. However, due to high-temperature combustion, the gallium-containing phase in fly ash is more stable, and it is difficult to separate gallium from it by simple leaching. In addition, the main element that can be extracted from fly ash is aluminum, and gallium is separated as a by-product, and the recovery rate is not high. Whether it is an alkaline process or an acid process, it must go through a complex activation, leaching, and impurity removal process to obtain a product with better purity. In addition, a large amount of acid and alkali materials are required in the process, which not only causes a large amount of difficult-to-treat waste liquid, but also the product obtained is only a gallium-rich solution that needs to be extracted by other methods. The cost of the entire process is difficult to control and cannot be applied to industrial production. Summary of the invention

[0005] In view of the problems existing in the prior art, the purpose of the present invention is to provide a pre-enrichment and activation process for gallium-containing coal gangue to solve the problem that gallium in coal gangue needs to be activated after enrichment before leaching or pyrometallurgy.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] The present invention provides a pre-enrichment and activation process for gallium-containing coal gangue, the pre-enrichment and activation process comprising:

[0008] The degraded coal gangue material, the first auxiliary agent and the second auxiliary agent are mixed, and then sintered to obtain a pre-enriched activated gallium-containing coal gangue sintered material;

[0009] The first auxiliary agent includes sodium material and boron material;

[0010] The second auxiliary agent includes aluminum material and a mixed material; the mixed material includes a IIA group element material and / or an IVB group element material.

[0011] The pre-enrichment and activation process provided by the present invention, with the help of a specific auxiliary agent system, can enrich the gallium element in the coal gangue into a specific phase without complicated enrichment means such as sorting and flotation, and simultaneously realize activation for subsequent separation and extraction, thereby achieving effective utilization of various useful components.

[0012] As a preferred technical solution of the present invention, the degraded coal gangue material is obtained by heat treating the coal gangue raw material.

[0013] Preferably, the heat treatment temperature is 500-650°C.

[0014] Preferably, the heat treatment time is 1-3 hours.

[0015] Preferably, the heating rate of the heat treatment is 8-15°C / min.

[0016] Preferably, the particle size of the coal gangue raw material is ≤0.5 mm.

[0017] As a preferred technical solution of the present invention, the mass ratio of the sodium material to the boron material in the first auxiliary agent is (1-3):1.

[0018] As a preferred technical solution of the present invention, the mass ratio of the aluminum material to the mixed material in the second auxiliary agent is (1-4):1.

[0019] As a preferred technical solution of the present invention, the aluminum material includes aluminum salt and / or aluminum hydroxide.

[0020] As a preferred technical solution of the present invention, the Group IIA element material is magnesium material and / or calcium material.

[0021] Preferably, the magnesium material comprises one or a combination of at least two of magnesium oxide, magnesium hydroxide or magnesium salt.

[0022] Preferably, the calcium material includes one or a combination of at least two of calcium oxide, calcium hydroxide or calcium salt.

[0023] Preferably, the Group IVB element material includes a titanium material and / or a zirconium material.

[0024] Preferably, the titanium material includes one or a combination of at least two of titanium oxide, titanium hydroxide or titanium salt.

[0025] Preferably, the zirconium material comprises one or a combination of at least two of zirconium oxide, zirconium hydroxide or zirconium salt.

[0026] As a preferred technical solution of the present invention, the mass ratio of the degraded coal gangue material to the first auxiliary agent is (8-10):1.

[0027] As a preferred technical solution of the present invention, the mass ratio of the degraded coal gangue material to the second auxiliary agent is (15-20):1.

[0028] As a preferred technical solution of the present invention, the sintering temperature is 700-1050°C.

[0029] Preferably, the sintering time is 2-5 hours.

[0030] Preferably, the heating rate of the sintering is 10-12°C / min.

[0031] Preferably, the sintering is performed under atmospheric conditions.

[0032] As a preferred technical solution of the present invention, the mixed material is molded before sintering, and a binder is added to the mixture at this time.

[0033] Preferably, the added amount of the binder is 5-6% of the mass of the degraded coal gangue material.

[0034] Compared with the prior art solutions, the present invention has the following beneficial effects:

[0035] In the pre-enrichment activation process provided by the present invention, the decontamination step only needs to remove organic matter such as C and S in the gangue, and there is no need to add a large amount of alkaline materials to remove silicon or separate other metal oxides with acidic materials in advance. The gallium component in the gangue is enriched with the help of subsequent specific additives, while the high amorphous phase is maintained in the gangue, so that the gallium in the gangue after activation is easier to migrate and separate, which is conducive to the efficient utilization of the gallium component. DETAILED DESCRIPTION

[0036] To better illustrate the present invention and facilitate understanding of the technical solution of the present invention, typical but non-limiting embodiments of the present invention are as follows:

[0037] This embodiment provides a pre-enrichment and activation process for gallium-containing coal gangue, and the pre-enrichment and activation process comprises:

[0038] The degraded coal gangue material, the first auxiliary agent and the second auxiliary agent are mixed, and then sintered to obtain a pre-enriched activated gallium-containing coal gangue sintered material;

[0039] The first auxiliary agent includes sodium material and boron material;

[0040] The second auxiliary agent includes aluminum material and a mixed material; the mixed material includes a IIA group element material and / or an IVB group element material.

[0041] Specifically, the degraded coal gangue material is obtained by heat treating the coal gangue raw material.

[0042] Specifically, the temperature of the heat treatment is 500-650°C, for example, it can be 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C or 650°C, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0043] Specifically, the heat treatment time is 1-3h, for example, it can be 1h, 1.2h, 1.4h, 1.6h, 1.8h, 2h, 2.2h, 2.4h, 2.6h, 2.8h or 3h, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0044] Specifically, the heating rate of the heat treatment is 8-15°C / min, for example, it can be 8°C / min, 9°C / min, 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min or 15°C / min, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0045] Specifically, the particle size of the coal gangue raw material is ≤0.5mm. It refers to particles of any size within this range, which may be aggregates of particles of a single particle size, such as aggregates of particles with a particle size of 0.2mm, such as aggregates of particles with a particle size of 0.3mm, such as aggregates of particles with a particle size of 0.4mm, or aggregates of all particles within a certain particle size range, such as aggregates of all particles within a particle size range of 0.2-0.3mm, such as aggregates of all particles within a particle size range of 0.01-0.3mm, such as aggregates of all particles within a particle size range of 0.1-0.2mm, such as aggregates of all particles within a particle size range of 0.08-0.5mm, etc.

[0046] Specifically, the mass ratio of the sodium material and the boron material in the first auxiliary agent is (1-3):1, for example, it can be 1:1, 1.2:1, 1.4:1, 1.6:1, 1.8:1, 2:1, 2.2:1, 2.4:1, 2.6:1, 2.8:1 or 3:1, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0047] In the present invention, the sodium material can be selected as sodium salt and / or sodium alkali, such as sodium salt can be sodium carbonate, sodium bicarbonate, and sodium alkali can be sodium hydroxide.

[0048] In the present invention, the boron material is boric acid and / or borate, and the borate is sodium borate and / or potassium borate.

[0049] Specifically, the mass ratio of the aluminum material to the mixed material in the second additive is (1-4):1, for example, it can be 1:1, 1.2:1, 1.4:1, 1.6:1, 1.8:1, 2:1, 2.2:1, 2.4:1, 2.6:1, 2.8:1, 3:1, 3.2:1, 3.4:1, 3.6:1, 3.8:1 or 4:1, etc., but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0050] Specifically, the aluminum material includes aluminum salt and / or aluminum hydroxide.

[0051] Wherein, the aluminum salt can be selected from aluminum sulfate, aluminum chloride, aluminum nitrate and the like.

[0052] Specifically, the Group IIA element material is a magnesium material and / or a calcium material.

[0053] The magnesium material includes one or a combination of at least two of magnesium oxide, magnesium hydroxide or magnesium salt.

[0054] Among them, magnesium oxide is magnesium oxide; magnesium hydroxide is magnesium hydroxide; magnesium salt is magnesium chloride, magnesium nitrate, magnesium sulfate and the like.

[0055] Wherein, the calcium material includes one or a combination of at least two of calcium oxide, calcium hydroxide or calcium salt.

[0056] Among them, calcium oxides include calcium oxide and calcium peroxide; calcium hydroxides include calcium hydroxide; calcium salts include calcium chloride, calcium carbonate, calcium fluoride, etc.

[0057] Wherein, the IVB group element material includes titanium material and / or zirconium material.

[0058] The titanium material includes one or a combination of at least two of titanium oxide, titanium hydroxide or titanium salt.

[0059] Among them, titanium oxides include titanium dioxide; titanium hydroxides include ferric hydroxide; titanium salts include titanium carbonate, titanium sulfate, etc., or titanates include calcium titanate, etc.

[0060] The zirconium material includes one or a combination of at least two of zirconium oxide, zirconium hydroxide or zirconium salt.

[0061] Among them, the zirconium oxide is zirconium oxide; the zirconium hydroxide is zirconium hydroxide; the zirconium salt is zirconium chloride, zirconium fluoride and the like.

[0062] Furthermore, the aforementioned related metal salts may also be organic acid salts, such as aluminum acetate, zirconium acetate, magnesium acetate, and the like.

[0063] Specifically, the mass ratio of the degraded coal gangue material and the first auxiliary agent is (8-10):1, for example, it can be 8:1, 8.2:1, 8.4:1, 8.6:1, 8.8:1, 9:1, 9.2:1, 9.4:1, 9.6:1, 9.8:1 or 10:1, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0064] Specifically, the mass ratio of the degraded coal gangue material and the second additive is (15-20):1, for example, it can be 15:1, 15.5:1, 16:1, 16.5:1, 17:1, 17.5:1, 18:1, 18.5:1, 19:1, 19.5:1 or 20:1, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0065] Specifically, the sintering temperature is 700-1050°C, for example, it can be 700°C, 720°C, 740°C, 760°C, 780°C, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, 910°C, 920°C, 930°C, 940°C, 960°C, 980°C, 1000°C, 1020°C, 1040°C or 1050°C, etc., but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0066] Specifically, the sintering time is 2-5h, for example, it can be 2h, 2.2h, 2.4h, 2.6h, 2.8h, 3h, 3.2h, 3.4h, 3.6h, 3.8h, 4h, 4.2h, 4.4h, 4.6h, 4.8h or 5h, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0067] Specifically, the sintering heating rate is 10-12°C / min, for example, it can be 10°C / min, 10.2°C / min, 10.4°C / min, 10.6°C / min, 10.8°C / min, 11°C / min, 11.2°C / min, 11.4°C / min, 11.6°C / min, 11.8°C / min or 12°C / min, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0068] Specifically, the sintering is performed under atmospheric conditions.

[0069] The atmosphere condition is an oxidizing atmosphere or a reducing atmosphere; the volume content of the oxidizing gas in the oxidizing atmosphere is ≤20%, such as oxygen and / or ozone; the volume content of the reducing gas in the reducing atmosphere is ≤14%, and the reducing gas can be selected as carbon monoxide and / or hydrogen; the gas concentration of the atmosphere can be adjusted with the help of inert gas or nitrogen, or other gases that do not affect the reaction process.

[0070] Furthermore, the mixed material is molded before sintering, and a binder is added to the mixture.

[0071] In the present invention, the binder can be selected from commonly used binders in molding in the art, such as polyvinyl alcohol, etc., to ensure the molding effect.

[0072] In the present invention, the molecular weight of the polyvinyl alcohol is selected to be 13000-23000.

[0073] Specifically, the amount of the binder added is 5-6% of the mass of the degraded coal gangue material, for example, it can be 5%, 5.2%, 5.4%, 5.6%, 5.8% or 6%, etc., but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0074] In the present invention, the main mineral phases in the selected coal gangue raw material are kaolinite (mass percentage ≥40%), boehmite, illite, mica and feldspar, etc.; the Al oxide content in the coal gangue raw material is 20-35%, and the Si oxide content is in the range of 25-40% (in mass percentage); the C content in the raw material is ≤30%, and the S content is ≤20% (in mass percentage); it also contains a small amount of Fe, Ca, Ti and other elements, and the mass fraction of each oxide is 1%-10% respectively; the Ga content in the coal gangue raw material is 20-200ppm.

[0075] The C and S contents in the degraded coal gangue obtained in the degraded step are both lower than 1%, and the decomposition rates of main minerals such as kaolinite and illite after degraded coal gangue are ≤30%; after sintering, the kaolinite is converted into metakaolinite and aluminosilicate spinel, and the decomposition rate of kaolinite is ≥60%.

[0076] In order to further illustrate the excellent performance of the pre-enrichment and activation process of gallium-containing coal gangue provided by the present invention, the following examples are specifically provided:

[0077] Example 1

[0078] This embodiment provides a pre-enrichment and activation process for gallium-containing coal gangue, and the pre-enrichment and activation process comprises:

[0079] The degraded coal gangue material, the first auxiliary agent and the second auxiliary agent are mixed, and then sintered to obtain a pre-enriched activated gallium-containing coal gangue sintered material;

[0080] The degraded gangue material is obtained by heat treating the gangue raw material; the heat treatment temperature is 600°C; the heat treatment time is 1.5h; the heating rate of the heat treatment is 12°C / min; the gangue raw material is an aggregate of all particles within a particle size of ≤0.4mm, that is, a product under a 0.4mm sieve;

[0081] The first auxiliary agent is potassium carbonate and boric acid; the mass ratio of the sodium material to the boron material in the first auxiliary agent is 1.8:1; the mass ratio of the degraded coal gangue material to the first auxiliary agent is 8.5:1;

[0082] The second auxiliary agent is aluminum hydroxide and magnesium sulfate; the mass ratio of aluminum material to magnesium material in the second auxiliary agent is 2:1; the mass ratio of the degraded coal gangue material to the second auxiliary agent is 17:1;

[0083] The mixed material is formed before sintering, and a binder (polyvinyl alcohol, molecular weight 13000) is added to the mixture; the amount of the binder added is 5% of the mass of the degraded coal gangue material;

[0084] The sintering temperature is 900° C.; the sintering time is 3 hours; the sintering heating rate is 11° C. / min; the sintering is carried out under an atmosphere containing nitrogen and oxygen, and the volume content of oxygen is 10%.

[0085] Example 2

[0086] This embodiment provides a pre-enrichment and activation process for gallium-containing coal gangue, and the pre-enrichment and activation process comprises:

[0087] The degraded coal gangue material, the first auxiliary agent and the second auxiliary agent are mixed, and then sintered to obtain a pre-enriched activated gallium-containing coal gangue sintered material;

[0088] The degraded gangue material is obtained by heat treating the gangue raw material; the heat treatment temperature is 550°C; the heat treatment time is 2h; the heating rate of the heat treatment is 10°C / min; the particle size of the gangue raw material is 0.1-0.5mm;

[0089] The first auxiliary agent is sodium carbonate and boric acid; the mass ratio of the sodium material to the boron material in the first auxiliary agent is 2.3:1; the mass ratio of the degraded coal gangue material to the first auxiliary agent is 9.4:1;

[0090] The second auxiliary agent is aluminum nitrate and magnesium hydroxide; the mass ratio of aluminum material to magnesium material in the second auxiliary agent is 3:1; the mass ratio of the degraded coal gangue material to the second auxiliary agent is 18:1;

[0091] The sintering temperature is 850° C.; the sintering time is 4 hours; the sintering heating rate is 10.5° C. / min; the sintering is carried out under an atmosphere of nitrogen and oxygen, with a volume content of oxygen of 5%.

[0092] Example 3

[0093] This embodiment provides a pre-enrichment and activation process for gallium-containing coal gangue, and the pre-enrichment and activation process comprises:

[0094] The degraded coal gangue material, the first auxiliary agent and the second auxiliary agent are mixed, and then sintered to obtain a pre-enriched activated gallium-containing coal gangue sintered material;

[0095] The degraded coal gangue material is obtained by heat treating the coal gangue raw material; the heat treatment temperature is 500°C; the heat treatment time is 3h; the heating rate of the heat treatment is 15°C / min; the particle size of the coal gangue raw material is ≤0.3mm;

[0096] The first auxiliary agent is potassium carbonate and boric acid; the mass ratio of the sodium material to the boron material in the first auxiliary agent is 3:1; the mass ratio of the degraded coal gangue material to the first auxiliary agent is 8:1;

[0097] The second auxiliary agent is aluminum carbonate and calcium oxide; the mass ratio of aluminum material to calcium material in the second auxiliary agent is 1:1; the mass ratio of the degraded coal gangue material to the second auxiliary agent is 20:1;

[0098] The mixed material is formed before sintering, and a binder (polyvinyl alcohol, molecular weight 23000) is added to the mixture; the amount of the binder added is 6% of the mass of the degraded coal gangue material;

[0099] The sintering temperature is 700° C.; the sintering time is 5 hours; the sintering heating rate is 12° C. / min; the sintering is carried out under an atmosphere of helium and hydrogen, and the volume concentration of hydrogen is 10%.

[0100] Example 4

[0101] This embodiment provides a pre-enrichment and activation process for gallium-containing coal gangue, and the pre-enrichment and activation process comprises:

[0102] The degraded coal gangue material, the first auxiliary agent and the second auxiliary agent are mixed, and then sintered to obtain a pre-enriched activated gallium-containing coal gangue sintered material;

[0103] The degraded coal gangue material is obtained by heat treating the coal gangue raw material; the heat treatment temperature is 650°C; the heat treatment time is 1h; the heating rate of the heat treatment is 8°C / min; the particle size of the coal gangue raw material is ≤0.5mm;

[0104] The first auxiliary agent is sodium carbonate and boric acid; the mass ratio of the sodium material to the boron material in the first auxiliary agent is 1:1; the mass ratio of the degraded coal gangue material to the first auxiliary agent is 10:1;

[0105] The second auxiliary agent is aluminum hydroxide and titanium sulfate; the mass ratio of aluminum material to titanium material in the second auxiliary agent is 4:1; the mass ratio of the degraded coal gangue material to the second auxiliary agent is 15:1;

[0106] The sintering temperature is 1050° C.; the sintering time is 2 hours; the sintering heating rate is 10° C. / min; the sintering is carried out under an atmosphere of helium and carbon monoxide, and the volume concentration of carbon monoxide is 5%.

[0107] Example 5

[0108] The only difference from Example 1 is that magnesium sulfate is replaced by an equal amount of zirconium oxide.

[0109] Example 6

[0110] The only difference from Example 1 is that magnesium sulfate is replaced by an equal amount of titanium dioxide.

[0111] Example 7

[0112] The difference from Example 1 is only that magnesium sulfate is replaced by an equal amount of calcium hydroxide.

[0113] Example 8

[0114] The difference from Example 1 is that magnesium sulfate is replaced by an equal amount of calcium chloride.

[0115] Example 9

[0116] The only difference from Example 1 is that magnesium sulfate is replaced by an equal amount of titanium hydroxide.

[0117] Example 10

[0118] The only difference from Example 1 is that magnesium sulfate is replaced by an equal amount of zirconium hydroxide.

[0119] Embodiment 11

[0120] The only difference from Example 1 is that magnesium sulfate is replaced by an equal amount of zirconium chloride.

[0121] Example 12

[0122] The only difference from Example 1 is that the magnesium sulfate in the second auxiliary agent is replaced by an equal amount of barium sulfate.

[0123] Comparative Example 1

[0124] The only difference from Example 1 is that the first auxiliary agent is not added.

[0125] Comparative Example 2

[0126] The only difference from Example 1 is that no second auxiliary agent is added.

[0127] Comparative Example 3

[0128] The only difference from Example 1 is that the aluminum material in the second auxiliary agent is replaced with an equal amount of magnesium material.

[0129] Comparative Example 4

[0130] The only difference from Example 1 is that the magnesium material in the second auxiliary agent is replaced by an equal amount of aluminum material.

[0131] Comparative Example 5

[0132] The only difference from Example 1 is that the magnesium sulfate in the second auxiliary agent is replaced by an equal amount of iron sulfate.

[0133] Comparative Example 6

[0134] The only difference from Example 1 is that the boric acid in the first auxiliary agent is replaced by an equal amount of magnesium sulfate.

[0135] Comparative Example 7

[0136] The only difference from Example 1 is that the sintering is performed under a nitrogen atmosphere.

[0137] The pre-enriched and activated gallium-containing coal gangue sintered materials obtained in Examples 1-12 and Comparative Examples 1-7 were reused for a second time. Specifically, the pre-enriched and activated gallium-containing coal gangue obtained in Examples 1-12 and Comparative Examples 1-7 were leached with sulfuric acid having a mass concentration of 20% at a solid-liquid ratio of 1:15 g / mL. For comparison, the present invention also provides a leaching experiment directly on the coal gangue raw material. The leaching-related parameters are the same as those in the embodiments. The leaching-related indicators are detailed in Table 1.

[0138] Table 1

[0139]

[0140]

[0141] Through the results of the above embodiments and comparative examples, it can be seen that the pre-enrichment activation process provided by the present invention, the obtained pre-enrichment material has a high amorphous phase content as a whole due to activation, wherein the main occurrence phase of gallium: kaolinite is converted into metakaolinite with extremely low crystallinity; pyrite is converted into iron oxide; and the titanium-containing ore phase is further stably converted into anatase. The presence of the high amorphous phase makes it easier for gallium to migrate and separate in the activated sintered material, which can be used for further high-temperature sintering migration and aggregation, thereby forming a single phase of gallium to achieve efficient enrichment and separation. In addition, alumina and silicon dioxide with higher purity can be obtained, which can achieve gallium separation while reducing waste slag production; at the same time, the activated coal gangue sintered material can also be used for wet leaching, separation, and extraction in the conventional method of extracting gallium from fly ash. When wet leaching is performed, the gallium leaching rate can reach more than 70%.

[0142] It is stated that the present invention illustrates the detailed structural features of the present invention through the above embodiments, but the present invention is not limited to the above detailed structural features, that is, it does not mean that the present invention must rely on the above detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0143] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0144] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0145] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A pre-enrichment and activation process for gallium-containing coal gangue, characterized in that: The pre-enrichment activation process comprises: The degraded coal gangue material, the first auxiliary agent and the second auxiliary agent are mixed, and then sintered to obtain a pre-enriched activated gallium-containing coal gangue sintered material; The first auxiliary agent includes sodium material and boron material; The second auxiliary agent includes aluminum material and a mixed material; the mixed material includes a IIA group element material and / or an IVB group element material.

2. The pre-enrichment activation process according to claim 1, characterized in that: The degraded coal gangue material is obtained by heat treating the coal gangue raw material; Preferably, the temperature of the heat treatment is 500-650°C; Preferably, the heat treatment time is 1-3h; Preferably, the heating rate of the heat treatment is 8-15°C / min; Preferably, the particle size of the coal gangue raw material is ≤0.5 mm.

3. The pre-enrichment activation process according to claim 1 or 2, characterized in that: The mass ratio of the sodium material to the boron material in the first auxiliary agent is (1-3):

1.

4. The pre-enrichment activation process according to any one of claims 1 to 3, characterized in that: The mass ratio of the aluminum material to the mixed material in the second auxiliary agent is (1-4):

1.

5. The pre-enrichment activation process according to any one of claims 1 to 4, characterized in that: The aluminum material includes aluminum salt and / or aluminum hydroxide.

6. The pre-enrichment activation process according to any one of claims 1 to 5, characterized in that: The Group IIA element material magnesium material and / or calcium material; Preferably, the magnesium material comprises one or a combination of at least two of magnesium oxide, magnesium hydroxide or magnesium salt; Preferably, the calcium material comprises one or a combination of at least two of calcium oxide, calcium hydroxide or calcium salt; Preferably, the IVB group element material includes titanium material and / or zirconium material; Preferably, the titanium material comprises one or a combination of at least two of titanium oxide, titanium hydroxide or titanium salt; Preferably, the zirconium material comprises one or a combination of at least two of zirconium oxide, zirconium hydroxide or zirconium salt.

7. The pre-enrichment activation process according to any one of claims 1 to 6, characterized in that: The mass ratio of the degraded coal gangue material to the first auxiliary agent is (8-10):

1.

8. The pre-enrichment activation process according to any one of claims 1 to 7, characterized in that: The mass ratio of the degraded coal gangue material to the second auxiliary agent is (15-20):

1.

9. The pre-enrichment activation process according to any one of claims 1 to 8, characterized in that: The sintering temperature is 700-1050°C; Preferably, the sintering time is 2-5h; Preferably, the heating rate of the sintering is 10-12°C / min; Preferably, the sintering is performed under atmospheric conditions.

10. The pre-enrichment activation process according to any one of claims 1 to 9, characterized in that: The mixed material is formed before sintering, and a binder is added to the mixture; Preferably, the added amount of the binder is 5-6% of the mass of the degraded coal gangue material.

Citation Information

Patent Citations

  • Coal gangue treatment method

    CN116286127A